Face Pose Estimation From Video Sequence Using Dynamic Bayesian Network. - A. Suandi, Shahrel; Enokida, Shuichi; Ejima, Toshiaki (2008)

(untitled)
This paper describes a technique to estimate human face pose from colour video sequence using Dynamic Bayesian Network(DBN). As face and facial features trackers usually track eyes, pupils, mouth corners and skin region(face), our proposed method utilizes merely three of these features – pupils, mouth centre and skin region – to compute the evidence for DBN inference.